QUALITY OF HIGHER EDUCATION: INTERNATIONAL DISCOURSE - Durdas, Alla; Kravchuk, Tetiana (Educological discourse, 2022)
The article deals with the state of research of the concept of higher education quality in Ukraine and other countries of the world. The issue of assessment of university education quality has been defined as the insufficiently studied phenomenon in the domestic and foreign scientific literature and, therefore, it requires further research. It has been found out that the world community considers high-quality higher education as a tool for social, cultural and economic growth. The article stresses that nowadays there is no country which would be satisfied with its higher education system, and the search for innovations for provision tangible results continues. The views of the scientists on higher education quality have been revealed: higher education quality is considered as a set of qualities of a person with higher education that reflects his or her professional competence, value orientation, social orientation and determines the ability of higher education to satisfy both personal spiritual and material needs, as well as the needs of society.